فعالية تطبيق نموذج التعليم PAIR CHECK بالطريقة السمعية الشفهية لترقية مهارة الإستماع والكلام لطلاب الفصل الثامن بمدرسة دار العلوم المتوسطة الإسلامية وارو سدووارجو - Kholifah, Siti Nur; Nu’man, Muhammad (Prodi Pendidikan Bahasa Arab FTK UIN Sunan Ampel, 2019)
The process of learning Arabic in MTS Darul Ulum Sidoarjo is still traditional and students find it difficult to understand subject matter especially listening ' and speaking. The purpose of this study are: (1) To find out the special skills and greetings of students of class VIII at MTs Darul Ulum Sidoarjo. (2) To find out the application of the PAIR CHECK model